2010
DOI: 10.1016/j.ultrasmedbio.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microbubble Size on Fundamental Mode High Frequency Ultrasound Imaging in Mice

Abstract: High-frequency ultrasound imaging using microbubble (MB) contrast agents is becoming increasingly popular in pre-clinical and small animal studies of anatomy, flow and vascular expression of molecular epitopes. Currently, in vivo imaging studies rely on highly polydisperse microbubble suspensions, which may provide a complex and varied acoustic response. In order to study the effect of individual microbubble size populations, microbubbles of 1-2 μm, 4-5 μm, and 6-8 μm diameter were isolated using the technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 42 publications
6
145
0
Order By: Relevance
“…Second, some time is necessary for the permeation and aggregation of the NBs; this requirement explains why the TTP of the NBs was later than that of the control MBs, which were too large to fit through the endothelial gaps. Third, because of their small size, the NBs were expected to absorb high-frequency ultrasound to a greater degree than their scattering at the fundamental frequency; 26 thus, the NBs exhibited a lower peak intensity in this study. Finally, their small size and PEGylated lipid shells helped the NBs escape from the mononuclear phagocyte system.…”
Section: Discussionmentioning
confidence: 91%
“…Second, some time is necessary for the permeation and aggregation of the NBs; this requirement explains why the TTP of the NBs was later than that of the control MBs, which were too large to fit through the endothelial gaps. Third, because of their small size, the NBs were expected to absorb high-frequency ultrasound to a greater degree than their scattering at the fundamental frequency; 26 thus, the NBs exhibited a lower peak intensity in this study. Finally, their small size and PEGylated lipid shells helped the NBs escape from the mononuclear phagocyte system.…”
Section: Discussionmentioning
confidence: 91%
“…This would result in a loss of core mass leading to a slightly smaller vaporized bubble. Nevertheless, the size distribution is well-maintained through the condensation and laser induced vaporization process; an important feature of the agents for dual mode imaging applications where strong scattering from the vaporized droplet population is desired [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies have been performed in rat (13,31,41), rabbit (59), dog (63,64,68), swine (24,69), mouse (55,57), and isolated organs (54). Contrast ultrasound imaging of the kidney is not in widespread clinical use, although studies have demonstrated potential utility for evaluation of focal abnormalities (46) and in identifying rejection following renal transplant (14,27,28).…”
Section: Discussionmentioning
confidence: 99%